2017
DOI: 10.21608/avmj.2017.166601
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Adenosine Deaminase (Ada) Level in Pregnant Ewes in Relation to Liver Function Test and Some Oxidant Indicator

Abstract: Pregnancy represents a major challenge to animal based on the analysis of immunological and metabolic responses. Thus, the aim of this study to assess the potential changes in adenosine deaminase (ADA) enzyme activity level, representative indicators of liver function, and some markers of oxidative stress. This study was conducted on 36 Saidi ewes divided into four equal groups (n=9). The first group (non pregnant) was kept as control, while the other three groups were classified according to the time interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…Additionally, the colostrum is noted to possess a significant quantity of GGT (Kaneko et al, 1997) and can also indicate an increase in metabolism related to high productivity (Nicolae et al, 2021). This study was similar to the data of Antunovic et al (2011) in Tsigai ewes, While in Saidi ewes, an increase in GGT levels is observed during the first trimester of pregnancy (Mohamed & Abou-Khali, 2017).…”
Section: The Effect Of Physiological State On Liver Parameterssupporting
confidence: 92%
“…Additionally, the colostrum is noted to possess a significant quantity of GGT (Kaneko et al, 1997) and can also indicate an increase in metabolism related to high productivity (Nicolae et al, 2021). This study was similar to the data of Antunovic et al (2011) in Tsigai ewes, While in Saidi ewes, an increase in GGT levels is observed during the first trimester of pregnancy (Mohamed & Abou-Khali, 2017).…”
Section: The Effect Of Physiological State On Liver Parameterssupporting
confidence: 92%